FOREIGN EXPERIENCE IN INSURANCE OF AGRICULTURAL RISKS THROUGH THE CREATION OF MUTUAL INSURANCE SOCIETIES (ResearchJet Journal of Analysis and Inventions, 2021)
The article describes the risks associated with the activities of agricultural enterprises, the features and benefits of their insurance through the creation of mutual insurance societies, as well as the Canadian experience as the experience of foreign countries with a long history, and recommendations are developed for the application of this experience in Uzbekistan.